FREEDOM OF MOVEMENT AND POSITIONING IN CHILDBIRTH WITH NON-INVASIVE TECHNOLOGIES OF NURSING CARE - Aline Caramez Costa; Juliana Amaral Prata; Karolayne Rosa Oliveira; Camilla Ribeiro Freitas da Silva; Jane Márcia Progianti; Ricardo José Oliveira Mouta; Adriana Lenho de Figueiredo Pereira (Universidade Federal do Paraná, 2023)
Objective: to identify the non-invasive technologies and care strategies used by obstetric nurses to encourage freedom of movement and positioning in the parturition process. Method: A descriptive and qualitative study, with 20 obstetric nurses working in public obstetric services in Rio de Janeiro - Brazil. Data were collected from May to July 2021 through semi-structured interviews and submitted to thematic analysis. Results: the participants use the encouragement to ambulate and perform pelvic movements and squats, also suggesting specific positions, especially vertical ones. As strategies, they orient about the benefits of these technologies and respect the choice of the expectant women, interfering, however, in cases of obstetric complications. Conclusion: The incentive to freedom of movement and positioning in parturition happens with the offer of different non-invasive technologies in a care relationship with clarified and shared decision-making processes, which promote autonomy and ensure the right to safe and respectful assistance.